Two New Genera of Jumping Spiders from Hainan Island, China (Araneae, Salticidae) - Zhou, Yuanye; Li, Shuqiang (Zootaxa, 2013)
Two new genera of the spider family Salticidae, Corusca gen. nov. and Insula gen. nov., are described. Nine new species of the genus Corusca gen. nov. and 11 new species of the genus Insula gen. nov. are reported from Hainan, Southern China: Corusca acris sp. nov. (male), C. bawangensis sp. nov. (male), C. falcata sp. nov. (male), C. gracilis sp. nov. (male and female), C. jianfengensis sp. nov. (male and female), C. sanyaensis sp. nov. (male and female), C. setifera sp. nov. (male and female), C. viriosa sp. nov. (male and female), C. wuzhishanensis sp. nov. (male and female), Insula curva sp. nov. (male and female), I. hebetata sp. nov. (male and female), I. limuensis sp. nov. (male and female), I. longa sp. nov. (male and female), I. minuta sp. nov. (male and female), I. nigricula sp. nov. (male and female), I. ramosa sp. nov. (male and female), I. scutata sp. nov. (male and female), I. squamata sp. nov. (male and female), I. tumida sp. nov. (male and female), I. uncinata sp. nov. (male and female). The males of two known species, Corusca liaoi (Peng & Li, 2006) and Insula maculata (Peng & Kim, 1997), which are transferred from Eupoa, are reported for the first time.